Abuse liability of intravenous buprenorphine vs. buprenorphine/naloxone: Importance of absolute naloxone amount. (1st October 2017) - Jones, Jermaine D.; Manubay, Jeanne M.; Mogali, Shanthi; Metz, Verena E.; Madera, Gabriela; Martinez, Suky; Mumtaz, Mudassir; Comer, Sandra D.
Highlights: Intravenous (IV) Buprenorphine (Bup) produced positive subjective effects antagonized with the addition of Naloxone (Nx). Bup + Nx combinations have reduced IV abuse potential in comparison to Bup alone. All IV Bup + Nx doses increased ratings of "Bad" drug effect and opioid withdrawal. Bup + Nx doses with more absolute Nx amounts produced more aversive effects. Bup + Nx formulations with greater absolute amounts of naloxone may be less abusable. Abstract: Background: This study sought to determine the relative importance of a range of Bup/Nx doses compared to Bup alone in producing subjective and reinforcing effects. Methods: Heroin-using volunteers (n = 13) were transitioned onto daily oral hydromorphone (40 mg). Laboratory sessions assessed the reinforcing and subjective effects of intravenous (IV) doses of Bup (1.51, 2.16, 6.15, and 8.64 mg) and Bup/Nx (1.51/0.44, 2.16/0.61, 6.15/1.71, and 8.64/2.44 mg). Placebo (Pbo), heroin (25 mg) and Nx (0.3 mg) were tested as neutral, positive, and negative controls, respectively. Results: IV Bup alone was self-administered substantially less than IV heroin, though the two largest doses of Bup produced positive subjective effects, drug "Liking" (0–100 mm), which were comparable to heroin (mean difference: Heroin vs Bup 6.15 mg: −3.4 mm, Heroin vs Bup 8.64 mg: −11.3 mm). All indicators of abuse potential seen with IV Bup alone were substantially decreased with the addition of Nx. All Bup/Nx combinations produced ratings of aversive effects, "Bad", which were comparable to, or greater than IV, Nx. On three of the four measures of aversive effects, the largest difference is seen with the 8.64 vs 8.64/2.44 condition. Conclusions: This study further demonstrates the ability of the Bup/Nx combination to deter IV use. Although none of the Bup/Nx combinations showed indications of abuse potential, formulations with larger absolute Nx, may be less abusable as they precipitate a greater degree of withdrawal.